Preparation of Smooth Surface TiO2 Photoanode for High Energy Conversion Efficiency in Dye-Sensitized Solar Cells. (20th May 2013) - Kathirvel, Sasipriya; Chen, Huei-Siou; Su, Chaochin; Wang, Hsiue-Hsyan; Li, Chung-Yen; Li, Wen-Ren
Abstract : Dye-sensitized solar cells (DSSCs) based on a TiO2 photoanode have been considered as an alternative source in the field of renewable energy resources. In DSSCs, photoanode plays a key role to achieve excellent photo-to-electric conversion efficiency. The surface morphology, surface area, TiO2 crystal phase, and the dispersion of TiO2 nanoparticles are the most important factors influencing the properties of a photoanode. The smooth TiO2 surface morphology of the photoanode indicates closely packed arrangement of TiO2 particles which enhance the light harvesting efficiency of the cell. In this paper, a smooth TiO2 photoanode has been successfully prepared using a well-dispersed anatase TiO2 nanosol via a simple hydrothermal process. The above TiO2 photoanode was then compared with the photoanode made from commercial TiO2 nanoparticle pastes. The morphological and structural analyses of both the aforementioned photoanodes were comprehensively characterized by scanning electron microscopy and X-ray diffraction analysis. The DSSC fabricated by using a-TiO2 nanosol-based photoelectrode exhibited an overall light conversion efficiency of 7.20% and a short-circuit current density of 13.34 mA cm −2, which was significantly higher than those of the DSSCs with the TiO2 nanoparticles-based electrodes.